Controlled preparation of M(Ag, Au)/TiO2 through sulfydryl-assisted method for enhanced photocatalysis. (23rd October 2017) - Xia, Hongbo; Wu, Suli; Bi, Jiajie; Zhang, Shufen
Abstract: Here a simple and effective method was explored to fabricate M/TiO2 (M = Ag, Au) composites, which required neither pre-treatment of TiO2 nor any additives as reducing agent. Using amorphous TiO2 spheres functionalized with SH groups as starting materials, the noble metallic ions (Ag, Au) can be adsorbed by TiO2 due to their special affinity with SH groups, which is beneficial to the uniform dispersion of metallic ions on the surface of TiO2 . Then the adsorbed ions were reduced to form noble metal nanoparticles by heating process (95 °C) directly without additive as reduction agent. Meanwhile, the amorphous TiO2 was transformed into anatase phase during the heating process. Thus, the transformation of TiO2 along with the reduction of noble metallic ions (Ag, Au) was simultaneously carried out by heating. The XRD patterns proved the formation of anatase TiO2 after heating. The characterizations of XPS and TEM proved the formation of Ag and Au nanoparticles on the surface of TiO2 . The element mapping indicated that Ag nanoparticles are dispersed uniformly on the surface of TiO2 . The photocatalytic activity of the composites has been investigated by the degradation of methyl orange under visible light irradiation. The results showed that when Ag/TiO2 (2.8 wt%) was used as photocatalyst, about 98% of the MO molecules were degraded in 70 min.